Cre recombinase expression or topical tamoxifen treatment do not affect retinal structure and function, neuronal vulnerability or glial reactivity in the mouse eye. (14th June 2016) - Boneva, S.K.; Groß, T.R.; Schlecht, A.; Schmitt, S.I.; Sippl, C.; Jägle, H.; Volz, C.; Neueder, A.; Tamm, E.R.; Braunger, B.M.
Highlights: Cre or tamoxifen do not influence neuronal morphology and function. Cre or tamoxifen do not induce macro- and microglia cell reactivity. Expression of neuroprotective factors is not influenced by Cre or tamoxifen. Cre or tamoxifen do not alter neuronal vulnerability. Abstract: Mice with a constitutive or tamoxifen-induced Cre recombinase (Cre) expression are frequently used research tools to allow the conditional deletion of target genes via the Cre-loxP system. Here we analyzed for the first time in a comprehensive and comparative way, whether retinal Cre expression or topical tamoxifen treatment itself would cause structural or functional changes, including changes in the expression profiles of molecular markers, glial reactivity and photoreceptor vulnerability. To this end, we characterized the transgenic α-Cre, Lmop-Cre and the tamoxifen-inducible CAGG-CreER™ mouse lines, all having robust Cre expression in the neuronal retina. In addition, we characterized the effects of topical tamoxifen treatment itself in wildtype mice. We performed morphometric analyses, immunohistochemical staining, in vivo ERG and angiography analyses and realtime RT-PCR analyses. Furthermore, the influence of Cre recombinase or topical tamoxifen exposure on neuronal vulnerability was studied by using light damage as a model for photoreceptor degeneration. Taken together, neither the expression of Cre, nor topical tamoxifen treatment caused detectable changes in retinal structure and function, the expression profiles of investigated molecular markers, glial reactivity and photoreceptor vulnerability. We conclude that the Cre-loxP system and its induction through tamoxifen is a safe and reliable method to delete desired target genes in the neural retina.